Analysis of business risk management implementationstudy on micro, small, medium enterprise - Melvin Louisly; Roby Tan; Febriani Fajar Wati; Mashita Ayuni; Ella Triana (Junal Ilmu Manajemen, 2023)
This study aims to analyze the application of business risk management to Chika Laundry SMEs. Analysis of Chika Laundry SMEs is carried out by analyzing risks to finance, operations, marketing, and products. The methodology used in this study is a qualitative method with the results of data obtained from interviews, on the results of the analysis the author identified risks to Chika Laundry SMEs and obtained results from research showing the greatest risk, namely regarding financial risks that rely on personal capital so that it can cause businesses to stop, and also we provide solutions in the form of risk control such as preparing raw materials for 2 months in the future, and to anticipate business failure, namely inviting work partners to work together, and it is also hoped that this research will be useful for entrepreneurs and readers so they can apply business risk management in their businesses and also add information about the importance of business risk management. The urgency of the research is that with the potential development of the Chika Laundry MSME business, it is necessary to implement risk management so that Chika Laundry MSMEs know what risks will occur and have prepared solutions to overcome these risks, and of course this risk handling needs to be implemented properly and appropriately.